THE EFFECT OF THE BRICKS USED IN MASONRY WALLS ON CHARACTERISTIC PROPERTIES - Zengin, Basak; Kocak, Ali (YILDIZ TECHNICAL UNIV, 2017)
Conventional masonry walls serve as partition element or main load-bearer of masonry buildings and reinforced concrete components. Examination of the damages occurring in the walls has revealed the effect of the material used, laying technique and bond between the masonry unit and joint. This study examines the norm feature (hollow directions) of the fabricated brick and masonry brick preferred in conventional walls on laying of the wall. To do this, lime mortar and cement mortar, which are commonly used for joints, were used in laying wall with the two different types of bricks. The data obtained by applying lateral+vertical loading to four different walls manufactured were analyzed through data collection device to ensure that load-displacement diagram are obtained. The study has revealed the effect of the material used and placement direction of the brick on strength of the wall.
Keywords: Masonry wall; fabricated and masonry brick; mortar; load-displacement chart; STRENGTH; BUILDINGS; MORTARS; FAILURE; PRISMS; PERIOD; Engineering